A simple and rapid method for generating patterned co-cultures with stable interfaces. (July 2013) - Javaherian, Sahar; Li, Katherine J.; McGuigan, Alison P.
In native tissues, different cell types are organized into defined structures and architectures that are critical for correct tissue function. In vitro cellular patterning methods enable control over the spatial organization of cells, permitting, to some extent, the reproduction of native tissue structures and the generation of a more "in vivo—like" culture platform. While this is advantageous for applications such as drug screening, existing patterning methods are time-consuming, labor-intensive, and low-throughput. Here, we describe a novel medium-throughput patterning strategy for generating spatially controlled co-cultures of two cell types based on differential deposition of BSA solution in a tilted plate. Our method allows generation of homotypic and heterotypic co-cultures that are stable for at least seven days in culture. The reproducibility and consistency of this patterning technique, together with its low cost and ease of use, make it a promising cell culture platform for medium- to high—throughput screening using high-content imaging.